2022
DOI: 10.1016/j.psychres.2022.114433
|View full text |Cite
|
Sign up to set email alerts
|

Examining the association between the COVID-19 pandemic and self-harm death counts in four Canadian provinces

Abstract: Governments implemented lockdowns and other physical distancing measures to stop the spread of SARS-CoV-2 (COVID-19). Resulting unemployment, income loss, poverty, and social isolation, coupled with daily reports of dire news about the COVID-19 pandemic, could serve as catalysts for increased self-harm deaths (SHD). This ecological study examined whether observed SHD counts were higher than predicted SHD counts during the pandemic period in the Canadian provinces of Alberta, British Columbia, Ontario, and Québ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Research on suicidality during the COVID-19 pandemic is an ongoing process. Among those studies that have been published, Ehlman and colleagues [ 41 ] and the National Institute of Health [ 42 ] reported that overall suicide rates decreased between 2019 and 2020 following a dramatic increase between 2017 and 2018 [ 43 ]. Studies regarding subsequent changes in suicide trends during the COVID-19 pandemic provide variable results depending on region of focus.…”
Section: Introductionmentioning
confidence: 99%
“…Research on suicidality during the COVID-19 pandemic is an ongoing process. Among those studies that have been published, Ehlman and colleagues [ 41 ] and the National Institute of Health [ 42 ] reported that overall suicide rates decreased between 2019 and 2020 following a dramatic increase between 2017 and 2018 [ 43 ]. Studies regarding subsequent changes in suicide trends during the COVID-19 pandemic provide variable results depending on region of focus.…”
Section: Introductionmentioning
confidence: 99%